Analysis of Cumulative Damage for Shared Rock in a Neighborhood Tunnel under Cyclic Blasting Loading Using the Ultrasonic Test - Feng Cao; Sheng Zhang; Tonghua Ling (Shock and Vibration)
In blasting excavation of neighborhood tunnels, damage accumulation process in surrounding rock is inevitable. To explore the influence of damage accumulation of rock mass under multiple blasting loads, we analyzed the vibration damage accumulation process of ultrasonic wave velocity of rock mass in shared rock of Liuyuetian neighborhood tunnel through ultrasonic test. Moreover, the effects of cyclic blasting loads on damage to the shared rock in the neighborhood tunnel were discussed and reported. The results demonstrate that the damage accumulation to the shared rock in the neighborhood tunnel is generated after multicycle progressive blasting operations. Influenced by cyclic blasting loads during the posterior excavating tunnel, the damage range of shared rock at the anterior excavating tunnel is 1.2 to 1.4 m, and the damage range of shared rock at the posterior excavating tunnel is 2.2 to 2.4 m. The damage range of shared rock in the posterior excavating tunnel is about 1.71 to 1.83 times that in the anterior excavating tunnel. Under blasting load, the stress concentration zone of shared rock is close to the blasting excavating face and is mainly within 2 m along the longitudinal axis of the tunnel. With continuous advancement of the blasting excavating face, the stress concentration zone moves forward continuously, and a striped stress concentration zone, which is approximately 2 m deep, is formed gradually. Thus, a method was proposed to determine the damage range of shared rock in the neighborhood tunnel during blasting excavation, as well as the variation law of damage. The experiences and conclusions presented can be used as references in the design and construction of similar engineering projects in the future.